The features of structural remodeling of rat testicles at poststrumectomic hypothyroidism. - Нerasуmyuk, I. Ye.; Ilkiv, O. P. (Морфологія / Morphologia / Morfologìâ, 2016)
Introduction. The lack of thyroid hormones leads to the decrease in basal metabolism and violation of the functional state of different organs and systems. One of the leading places is occupied by the cardiovascular disorders which affect the state of gonads. Objective - to determine the nature of morphofunctional reorganization of rat testicles and features of their bloodstream remodeling after the strumectomy. Methods. The experiments were conducted on mature white male rats which underwent the strumectomy. The material for histology were taken after 1, 3, 7, 14 and 28 days after the surgery. Histological sections stained with hematoxylin and eosin, by Van Ghison method. Results. In 1 day after the strumectomy the arterial and venous plethora was observed, which was combined with stromal edema. 3 days after the surgical intervention the morphological signs of organ circulatory disorders were partially reduced. However, the stromal edema remained and was accompanied by reduce in number of cell layers in spermatogenic epithelium with the increasing of intervals between them and their detachment from the basement membrane. In seven days morphological manifestations of vascular responses became more obvious. One could observe the narrowing of the orifices of side branches of the small arteries from the trunks. Identified changes progressed up to 14 days. Arteries with particularly thick walls and narrowed lumen were often detected. In tubules the signs of fibrous transformation were detected. On the 28th day of experiment the signs of disorders of blood circulation and nourishment of testicles were further compounded. Seminiferous tubules looked devastated. Their fibrous transformation was observed with the growth of connective tissue in the interchannel intervals. Conclusion. After the strumectomy in the rat testicles it was observed the significant circulatory disorders of organ leading to the degenerative changes in the stroma and parenchyma. The progression of degenerative changes leads to the reduction of spermatogenic epithelium, fibrous transformation of seminiferous tubules with the growth of connective tissue in the interstices.